VIRTUAL PROFESSIONAL DEVELOPMENT FORUM FOR RURAL TEACHERS IN KALIMANTAN BARAT - Ikhsanudin Ikhsanudin (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2021)
This article analyzes the  prospect of developing a virtual learning forum to help rural English teachers capacity building. The forum is considered important to provide opportunities for the teachers to communicate, to share ideas and experiences, and to discuss amongst themselves and with teachers in more developed regions as well as with experts. The study was conducted qualitatively in Kalimantan Barat (West Kalimantan) province, Indonesia. The data were collected from four districts through observation and interview. A three-level classification system in qualitative survey design that consisted of unidimensional description, multidimensional description, and explanation was used to analyze the data. The study revealed that internet connection, transportation infrastructure, government regulations, and teacher readiness were important factors that would help the rural teachers develop virtual learning forums. The suitable mode that could support the forum was an asynchronous discussion forum using open social media groups. The challenge that would possibly be difficult to solve was finding highly motivated teachers to initiate and to manage the forums. The study recommends that teachers and experts from a university can mentor the motivated teacher leaders in the first year.